Descartes’ influence on Phenomenology - Žiemytė, Rasa (Problemos, 1998)
Descartes’ influence on phenomenology is revealed in the context of other persons by whom E. Husserl was influenced. Some general ideas of Descartes and Husserl (who both resemble each other and are also different from each other) are compared to the phenomenological perspective. Cartesian philosophy is criticised in a Husserlian manner.